2014
DOI: 10.1371/journal.pone.0096734
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Ischemic Postconditioning against Neuronal Apoptosis Induced by Transient Focal Ischemia Is Associated with Attenuation of NF-κB/p65 Activation

Abstract: Background and PurposeAccumulating evidences have demonstrated that nuclear factor κB/p65 plays a protective role in the protection of ischemic preconditioning and detrimental role in lethal ischemia-induced programmed cell death including apoptosis and autophagic death. However, its role in the protection of ischemic postconditioning is still unclear.MethodsRat MCAO model was used to produce transient focal ischemia. The procedure of ischemic postconditioning consisted of three cycles of 30 seconds reperfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…A major finding of this present study is that both NF-κB and MAPK(s) signaling pathways played a major role in the expression and activation of NLRP1 and NLRP3 inflammasomes in primary cortical neurons, and that the expression and activation of neuronal NLRP1 and NLRP3 inflammasomes was able to be attenuated by treatment with either NF-κB and MAPKs inhibitors under simulated in vitro ischemic conditions. Several previous studies have provided evidence that activation of both NF-κB and MAPK(s) signaling pathways occur in neurons following ischemic stroke Gladbach et al, 2014;Liang et al, 2014;Liu et al, 2009;. In the present study, we again provide supporting evidence that activation of both NF-κB and MAPK(s) signaling pathways are detrimental to neuronal survival and pharmacological inhibition of either the NF-κB and MAPK(s) signaling pathways were able to significantly protect neurons under ischemic conditions.…”
Section: Discussionsupporting
confidence: 87%
“…A major finding of this present study is that both NF-κB and MAPK(s) signaling pathways played a major role in the expression and activation of NLRP1 and NLRP3 inflammasomes in primary cortical neurons, and that the expression and activation of neuronal NLRP1 and NLRP3 inflammasomes was able to be attenuated by treatment with either NF-κB and MAPKs inhibitors under simulated in vitro ischemic conditions. Several previous studies have provided evidence that activation of both NF-κB and MAPK(s) signaling pathways occur in neurons following ischemic stroke Gladbach et al, 2014;Liang et al, 2014;Liu et al, 2009;. In the present study, we again provide supporting evidence that activation of both NF-κB and MAPK(s) signaling pathways are detrimental to neuronal survival and pharmacological inhibition of either the NF-κB and MAPK(s) signaling pathways were able to significantly protect neurons under ischemic conditions.…”
Section: Discussionsupporting
confidence: 87%
“…RIPostC is the application of “brief intermittent cycles of ischemia alternating with reperfusion” [ 26 ] in the limbs after an ischemic insult. RIPostC has been shown to reduce cerebral ischemia-induced infarct size and neuronal apoptosis in rats [ 27 ] and could be similarly effective in neonates. Whilst the underlying neuroprotective mechanism is yet to be understood, RIPostC may interfere with apoptotic pathways by reducing oxidative stress to indirectly inhibit NF- κ B activity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…IKB-alpha constitutes its inhibitory effect onto NF-kB through binding tightly to NF-kB dimers, forming a complex, masking the nuclear localization signals (NLS) and keeping the NF-kB sequestered in the cytoplasm [ 50 ]. Due to stressors like ischemia or hypoxia, during the acute phase there IkB-alpha gets activated when phosphorylated by IkB kinase (IKK) causing their eventual degradation by proteasomes [ 51 , 52 ]. The ischemia-induced increase of active IkB-alpha expression in the brain allows increased NF-kB expression and leads to neuroinflammatory responses, which can cause harmful post-stroke injury [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have attempted to determine how eliminating the upregulation of phosphorylated IkB-alpha and its subsequent degradation can affect post-ischemia recovery. Interestingly, several studies have shown that ischemic post conditioning, the use of flavonoids and stem cells therapy can reversed the phosphorylation and degradation levels of IkB-alpha caused by ischemia [ 51 , 52 , 54 , 55 ]. These studies support our finding whereby EPC graphs were able to reduce the overexpression of active IkB-alpha, typically seen after ischemic injury, in the peri-infarct area of cortex and striatum as depicted by immunofluorescent and further validated by protein analysis of the whole ipsilateral hemisphere.…”
Section: Discussionmentioning
confidence: 99%